2016
DOI: 10.1016/j.desal.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling and experimental validation for direct contact membrane distillation (DCMD) process

Abstract: This work proposes a mathematical dynamic model for the direct contact membrane distillation (DCMD) process. The model is based on a 2D Advection-Diffusion Equation (ADE), which describes the heat and mass transfer mechanisms that take place inside the DCMD module. The model studies the behavior of the process in the time varying and the steady state phases, contributing to understanding the process performance, especially when it is driven by intermittent energy supply, such as the solar energy. The model is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…All of these reasons have motivated the dynamical modeling of the MD process [3,13,14,15,16,17,18]. In [3,13] variations of the dynamic convection equation were considered to model air gap MD, whereas in [14,15,16] the 2D convection diffusion equation was used to model DCMD. On the other hand, [17] proposed a black-box model based on neural-networks for the permeate gap MD setup.…”
Section: Introductionmentioning
confidence: 99%
“…All of these reasons have motivated the dynamical modeling of the MD process [3,13,14,15,16,17,18]. In [3,13] variations of the dynamic convection equation were considered to model air gap MD, whereas in [14,15,16] the 2D convection diffusion equation was used to model DCMD. On the other hand, [17] proposed a black-box model based on neural-networks for the permeate gap MD setup.…”
Section: Introductionmentioning
confidence: 99%
“…According to the water vapor cooling-down method, the MD process can be classified into four different configurations [5]. By survey of the previous studies, it can be found that among these different MD processes, direct contact membrane distillation (DCMD) is the widely adopted configuration due to its simplicity and reasonably high water flux [32][33][34][35][36][37]. Therefore, in this study, DCMD configuration is used to evaluate the separation properties of the hydrophobic ceramic membranes prepared using the freeze drying tape casting method.…”
Section: Introductionmentioning
confidence: 99%
“…The transmembrane pressure (2 bar), crossflow velocity (2 m s ‐1 ) and temperature (25 °C) remained unchanged. In this way, it could be confirmed if the combined model predictions were accurate when a different whey model solution was used …”
Section: Resultsmentioning
confidence: 90%